Strategi Pembelajaran Inkuiri Guru Mata Pelajaran Fiqih pada Masa Pandemi Covid 19 di MI Nidhomiyah Sentul Tembelang Jombang - Dewi Fatimah Tuzahro; Didin Sirojudin (Universitas KH. A. Wahab Hasbullah, 2022)
This research was conducted during the COVID-19 pandemic where all schools used an online learning system or learning at home. As in MI Nidhomiyah Sentul, we took samples from fiqh subjects and the learning strategy used by fiqh teachers was inquiry learning strategy. What is done is by providing learning materials in the form of reading texts on textbooks or learning videos made by the teacher, after that students are asked to understand the content in the material by means of voicenotes, students do question and answer among their friends/discussions after all the teachers give assignments. to students. The impact of the changing learning system has resulted in teachers, students and parents experiencing their respective difficulties. Such as inadequate facilities for online learning, lack of internet network, parents who do not understand online learning and learning materials, and so on. This study uses qualitative research methods data obtained through interviews. Keywords:Covid-19 pandemic, learning strategies, impact